Self Care, Drug Taking Adherence, and their Association with Complication in Type 2 Diabetes Mellitus Patients - Widya Kaharani Putri; Setyo Sri Rahardjo; Dono Indarto (Journal of Epidemiology and Public Health, 2018)
Background: Diabetes mellitus (DM) is a major global health issue. The incidence of DM worldwide was about 6.4% (285 million people) in 2010 and it is projected to increase to 7.7% in 2030. Diabetes is associated with a number of challenges. The disease has a great influence on the patient